Protective effect of beta-glucan against oxidative organ injury in a rat model of sepsis - ERCAN, FERİHA; ŞENER, GÖKSEL (ELSEVIER, 2005)
Sepsis leads to various organ damage and dysfunction. One of the underlying mechanisms is thought to be the oxidative damage due to the generation of free radicals. In this study, we investigated the putative protective role of beta-gluican against sepsis-induced oxidative organ damage. Sepsis was induced by caecal ligation and puncture (CLP) in Wistar albino rats. Sham operated (control) and sepsis groups received saline or beta-glucan (50 mg/kg, po) once daily for 10 days and 30 min prior to and 6 h after the CLP. Sixteen hours after the surgery, rats were decapitated and the biochemical changes were determined in the brain, diaphragm, kidney, heart, liver and lung tissues using malondialdehyde (N4DA) content - an index of lipid peroxidation - glutathione (GSH) levels - a key antioxidant - and myeloperoxidase (MPO) activity - an index of neutrophil infiltration. Serum TNF-alpha levels were assessed by RIA method. Tissues were also examined under light microscope to evaluate the degree of sepsis-induced damage. The results demonstrate that sepsis significantly decreased GSH levels and increased the MDA levels and MPO activity (p < 0.05-p < 0.001) causing oxidative damage. Elevated plasma TNF-alpha levels in septic rats significantly reduced to control levels in beta-glucan treated rats. Since -glucan administration reversed these oxidant responses, it seems likely that beta-glucan protects against sepsis-induced oxidative organ injury. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: sepsis.; beta-glucan; lipid peroxidation; glutathione; myeloperoxidase activity; TNF-alpha; MYELOPEROXIDASE ACTIVITY; FREE-RADICALS; ACTIVATION; MELATONIN; RECEPTOR; EXPRESSION; TISSUE; GLUTATHIONE; CD11B/CD18; DECTIN-1